2019
DOI: 10.3389/fchem.2019.00110
|View full text |Cite
|
Sign up to set email alerts
|

Selective Electrochemical Conversion of Glycerol to Glycolic Acid and Lactic Acid on a Mixed Carbon-Black Activated Carbon Electrode in a Single Compartment Electrochemical Cell

Abstract: In recent years, the rapid swift increase in world biodiesel production has caused an oversupply of its by-product, glycerol. Therefore, extensive research is done worldwide to convert glycerol into numerous high added-value chemicals i.e., glyceric acid, 1,2-propanediol, acrolein, glycerol carbonate, dihydroxyacetone, etc. Hydroxyl acids, glycolic acid and lactic acid, which comprise of carboxyl and alcohol functional groups, are the focus of this study. They are chemicals that are commonly found in the cosme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 58 publications
0
34
0
Order By: Relevance
“…reported that strong alkali can promote this deprotonation step, since glycerol behaves as a weak acid in a strong alkaline solution whose pH is close to the pKa of glycerol (14.15). Once chemisorbed, a second deprotonation from the carbon atom occurs, which oxidizes glycerol into glyceraldehyde or DHA [19] . As in alkaline conditions OH- exists in the electrolyte, Pt‐OH(ads) (reportedly produced at 0.5 V–0.6 V vs RHE [20] ) can subsequently oxidize the chemisorbed glyceraldehyde into glyceric acid or glycerate.…”
Section: Summary Of Observed Glycerol Oxidation Results and Reported mentioning
confidence: 99%
See 1 more Smart Citation
“…reported that strong alkali can promote this deprotonation step, since glycerol behaves as a weak acid in a strong alkaline solution whose pH is close to the pKa of glycerol (14.15). Once chemisorbed, a second deprotonation from the carbon atom occurs, which oxidizes glycerol into glyceraldehyde or DHA [19] . As in alkaline conditions OH- exists in the electrolyte, Pt‐OH(ads) (reportedly produced at 0.5 V–0.6 V vs RHE [20] ) can subsequently oxidize the chemisorbed glyceraldehyde into glyceric acid or glycerate.…”
Section: Summary Of Observed Glycerol Oxidation Results and Reported mentioning
confidence: 99%
“…An overview of these hypotheses and controversies is therefore timely, and should be used to direct the future works. It is an area that has not yet been emphasized in previously published reviews [19–21] . The reaction mechanism of GEOR was partially reviewed by Gomes et al [22] .…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism pathways and reaction kinetics can be infl u enoed by overpotential, glycerol conversion, selectivity and yield of desired products, which could alter reaction parameters like activation energy barrier to stimulate fast molecular collision and surmount the binding energies of the reactants. For instance, an increase in temperature from 27 °C to 80 °C could accelerate the C C bond breakage, hence, converting glycerol into glycolic acid (Lee et al, 2019a). Lee et al (2019a) reported high glycolic acid yield (66.1%) with a selectivity of 72% after 6 h of reaction at 80 °C.…”
Section: Effect Of Parameters On Mechanism Pathways and Reaction Perfmentioning
confidence: 99%
“…For instance, an increase in temperature from 27 °C to 80 °C could accelerate the C C bond breakage, hence, converting glycerol into glycolic acid (Lee et al, 2019a). Lee et al (2019a) reported high glycolic acid yield (66.1%) with a selectivity of 72% after 6 h of reaction at 80 °C. Besides, the glycerol/catalyst molar ratio is a crucial param eter to attain high glyoerol conversion and products selectivity (Kim et al, 2017a).…”
Section: Effect Of Parameters On Mechanism Pathways and Reaction Perfmentioning
confidence: 99%
See 1 more Smart Citation